Crystallization and preliminary X-ray analysis of vicenisaminyltransferase VinC - Nango, Eriko (International Union of Crystallography, 2008)
A recombinant glycosyltransferase, VinC, from Streptomyces halstedii HC34 has been crystallized at 293 K using PEG 3350 as precipitant. The diffraction pattern of the crystal extends to 2.0 Å resolution at 100 K using synchrotron radiation at SPring-8. The crystals are orthorhombic and belong to space group I222, with unit-cell parameters a = 98.21, b = 130.39, c = 140.11 Å. The presence of two molecules per asymmetric unit gives a crystal volume per protein weight (V (M)) of 2.43 Å(3) Da(−1) and a solvent content of 49.5% by volume.